2020
DOI: 10.1007/s11606-020-05770-w
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Primary Care Physician Burnout and Patient-Reported Care Experiences: a Cross-sectional Study

Abstract: BACKGROUND: Primary care physician (PCP) burnout is prevalent and on the rise. Physician burnout may negatively affect patient experience of care. OBJECTIVE: To identify the direct impact of PCP burnout on patient experience in various domains of care. DESIGN: A cross-sectional observational study using physician well-being (PWB) surveys collected in 2016-2017, linked to responses from patient experience of care surveys. Patient demographics and practice characteristics were derived from the electronic health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 58 publications
0
35
0
1
Order By: Relevance
“…The experience of zero infection in medical aid team also proves the effective management in medical aid team, in the aspect of protective equipment. In addition, we can observe that the environment of management and public may be highly associated with the burnout and compassion satisfaction of HCWs [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The experience of zero infection in medical aid team also proves the effective management in medical aid team, in the aspect of protective equipment. In addition, we can observe that the environment of management and public may be highly associated with the burnout and compassion satisfaction of HCWs [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…At an institutional level, burnout affects the quality of healthcare. Studies show that doctors with burnout make more mistakes, 5 have reduced professional work effort, 6 have poorer patient–doctor communication 7 and self-report suboptimal care to patients. 4 Burnout has also been associated with increased days of work absenteeism, 8 increased intention to leave their work, 9 earlier retirement and reduced clinic hours.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study using a single-item measure of self-reported burnout found a negative association between primary care physician burnout and patient ratings of physician communication, but no association between burnout and overall patient rating of the physician. 36 Our finding suggests that there is a phenotype of very committed, hard-working, and exhausted clinicians who are perceived by patients to be excellent, patient-centered clinicians, despite the toll that this disposition may take on the clinician's wellbeing. The co-occurrence of high burnout and high engagement may be a characteristic of missiondriven individuals who prioritize the importance or impact of their work over considerations of worklife balance.…”
Section: Discussionmentioning
confidence: 74%
“…Response rates to the CG-CAHPS were 12% to 13%, which is consistent with rates reported by other organizations for routinely administered patient experience surveys. [35][36][37] CG-CAHPS measures for the clinicians in the study sample were derived from 9000 completed patient experience surveys, with a mean of 51 and a range of 5 to 325 patient responses per clinician. Consistent with CG-CAHPS reporting, the score at the clinician level for each item was computed as the percentage of survey respondents giving the clinician the highest possible rating for the measure.…”
Section: Methodsmentioning
confidence: 99%